The Kongming defense: Host-pathogen battles take a new face - Dongchun Ni (Engineering Microbiology)
Bacteria employ diverse immune systems, such as CRISPR-Cas, to fend off phage infections. A recent study uncovered the unprecedented mechanistic features of the Kongming bacterial defense system, which uniquely exploits phage-derived enzymes to synthesize deoxyinosine triphosphate (dITP), thereby triggering host immunity through NAD+ depletion. In response, some phages have evolved countermeasures to disrupt dITP synthesis, highlighting the ongoing evolutionary arms race between hosts and pathogens. This discovery not only deepens our understanding of bacterial defense strategies but also paves the way for new insights in biomedical research and synthetic biology.